PENYULUHAN TENTANG KESEHATAN REPRODUKSI DAN PEMERIKSAAN KESEHATAN BAGI MAHASISWI JURUSAN FISIOTERAPI POLTEKKES KEMENKES JAKARTA 3 - Ratu Karel Lina; Rovika Trioclarise; Ganesa Puput Dinda Kurniawan (Jurnal Pengabdian Masyarakat Fisioterapi dan Kesehatan Indonesia, 2023)
Background : Primary dysmenorrhea is a physical disorder characterized by feelings of pain in women who are menstruating in the form of abdominal pain/cramps that are not caused by pathological conditions of the gynecological system. The cramps are mainly felt in the lower abdominal area and spread to the back or inner surface of the thighs. This pain usually disrupts the student's learning process. Several non-pharmacological treatments can reduce pain intensity. To reduce the intensity of primary dysmenorrhea pain, low impact aerobic exercise can be done for students in the second semester of the Health Polytechnic, Ministry of Health, Jakarta 3. Objective: rovide knowledge about how to improve general health for students, carry out physical examinations related to general health and reproductive health, provide low impact aerobic exercise. Method: In this program, several activities are carried out including: preliminary studies, identification of personnel, facilities and infrastructure, counseling activities and health checks. Results: This Community Service activity consists of counseling on healthy behavior and the importance of regular exercise, Health Checks including checking blood pressure, pulse, respiratory rate and reproductive health checks. Carrying out demonstrations of low impact aerobic exercise and accompanying activities. This activity was carried out from September 2021 at the Health Polytechnic of the Ministry of Health, Jakarta 3. Conclusion: community service activities in the form of counseling about reproductive health were carried out well. Key words: knowledge, reproductive health